Permasalahan kasus kemiskinan di Kota Malang - Shobih, M . (Maliki Interdisciplinary Journal, 2024)
This article discusses the problem of poverty in Malang City, which is a complex problem triggered by various interrelated factors. This article also identifies three main factors that contribute to poverty in Malang City. The first factor is the rapid population growth without adequate jobs and infrastructure that can exacerbate poverty, the second is the low level of education that can limit a person's ability to get a decent job and earn a high income, and the third factor is the uneven economic development and lack of quality jobs that can exacerbate poverty. This article shows that the three factors are interrelated and the solution to overcome them must be comprehensive and sustainable, involving various parties.